Zonificación para captación de Co2 en bosques mediante uso de S.I.G. como aporte para la sostenibilidad ambiental de la microcuenca Cañas - Borrero Párraga, Carlos Javier (2017)
This vegetation cover in the forests of the watershed Canas Bolívar Canton province of Manabi is a mountainous territory, which is home to native forests and endemic plant species, with an area approximately 24Km2, the research was conducted during 12 months. Where the methodology proposed by Galeana-applied Pizaña et al., (2013) which allowed us to estimate carbon sequestration without altering the ecological balance of the area. Work in the field and the application of the above methodology was identified 15 species with DBH <1,30m., 5008 represented a total four individuals being the most abundant species Hevea brasiliensis the (18,89%), Pithecellobiun (14.40%), Phytelephas Aequatorialis (14.88%), Cordia alliodora (11.04%). These species account for 59.21% of total individuals. With DAP data> 1,30m. 39 species represented in a total 18030 individuals were sampled, considering the tree density area of the sub-samples of 1000m2 unit, represented at a density of 18.03 is expected. From this result the necessary equations given in the methodology for the total density of all the sampled area resulting 1.50 Biomass area referred to in an average total 2,15E + 01 was performed, and the same was obtained biomass total area was 1,785 using the allometric equation proposed by the IPCC (2003), resulted in 0,350, carbon sequestration was through biomass total area 0,215, determining the total value capture MGDM 0.1075 / MGC. Keywords: Biomass, collection, vegetation, red, square, Allometric, tree.